Contribution to the taxonomy of Paracloeodes Day 1955 (Ephemeroptera: Baetidae) from South America - Cruz, Paulo Vilela; Salles, Frederico Falcão; Hamada, Neusa (Zootaxa, 2018)
In recent decades, major advances in the systematics of the Western Hemisphere genus Paracloeodes Day have been made in South America. Despite the taxonomic progress, uncertainties in identification remain due to the morphological similarities among some nymphs and due to the general lack of knowledge of the imago stages (only 4 of 20 are described from throughout the range of the genus). This study addresses these impediments in part through description of the male imagoes of six species (P. atroari Nieto & Salles, P. binodulus Lugo-Ortiz & McCafferty, P. ibicui Lugo-Ortiz & McCafferty, P. pacawara Nieto & Salles, P. peri Nieto & Salles, P. waimiri Nieto & Salles), description of two new species based on morphologically distinct nymphs (P. aristotelesi sp. n. and P. carolinae sp. n.), description of one new species based on morphologically distinct nymph and male imago (P. prismatobranchus sp. n.); redescription of three species based on type material (P. ibicui Lugo-Ortiz & McCafferty, P. leptobranchus Lugo-Ortiz & McCafferty and P. eurybranchus Lugo-Ortiz & McCafferty); proposal of one new synonym based on morphological analyses of specimens from Bolivia, Brazil and Uruguay, including type specimens (P. pacawara = P. morellii Emmerich & Nieto); and the presentation of a new key to identify nymphs from South America to the species level.